2018
DOI: 10.1371/journal.pone.0193908
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diurnal variations, gestational age and gender related differences in fetal heart rate (FHR) parameters between appropriate-for-gestational-age (AGA) and small-for-gestational-age (SGA) fetuses in the home environment

Abstract: ObjectiveTo assess the influence of gender, time of the day and gestational age on fetal heart rate (FHR) parameters between appropriate-for-gestational-age (AGA) and small-for-gestational age (SGA) fetuses using a portable fetal ECG monitor employed in the home setting.MethodsWe analysed and compared the antenatal FHR data collected in the home setting on 61 healthy pregnant women with singleton pregnancies from 24 weeks gestation. Of the 61 women, 31 had SGA fetuses (estimated fetal weight below the tenth ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In 50 participants, the device did not record the FHR data either from the beginning (n = 30) or during the last hour of delivery (n = 20). Our previous works [22][23][24] and that of other investigators [8,9] have demonstrated the feasibility and accuracy of computerised FHR https://doi.org/10.1371/journal.pone.0236982.g002…”
Section: Discussionmentioning
confidence: 92%
“…In 50 participants, the device did not record the FHR data either from the beginning (n = 30) or during the last hour of delivery (n = 20). Our previous works [22][23][24] and that of other investigators [8,9] have demonstrated the feasibility and accuracy of computerised FHR https://doi.org/10.1371/journal.pone.0236982.g002…”
Section: Discussionmentioning
confidence: 92%
“…Ten of the 43 studies were from the UK [ 25 27 , 35 , 37 39 , 49 , 50 , 55 ], 22 from other European countries [ 24 , 28 33 , 36 , 40 , 42 44 , 48 , 51 54 , 56 , 57 , 61 , 64 , 65 ], five from Japan [ 41 , 59 , 60 , 62 , 63 ], one from India [ 45 ], one from Australia [ 66 ], three from the United States of America (USA) [ 46 , 47 , 58 ], and one study from both the Netherlands and USA [ 34 ]. The included studies were heterogeneous, they had a median sample size of 34.5 participants (range 1–657) and a median number of recordings of 63 (range 1–657).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-five out of the 43 studies were specifically concerned with a device to measure the FHR. Twenty-nine studies utilised only fECG devices, of which nine were unnamed [ 24 , 25 , 27 , 30 , 31 , 40 , 44 , 49 , 55 ] and the remaining 20 studies used either: Monica AN24 device [ 26 , 33 , 34 , 36 , 38 , 39 , 50 52 , 54 , 56 , 58 ]; Telefetalcare [ 28 , 29 , 53 ]; FECGV1 [ 35 ]; Cardiolab Babycard [ 43 ]; Nemo fetal monitor [ 48 , 57 ]; or Corometrics 112 abdominal ECG monitor [ 47 ]. Two studies used only fPCG devices, of which one was named the Fetaphon-2000 [ 42 ] and the other was unnamed [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is time to establish methodological standards concerning factors affecting FHRV analyses, to provide meaningful interpretation and comparison of results and consistency for future studies. Potential variables of importance include gestational age (Van Leeuwen et al, 2003 , 2013 ; Schneider et al, 2018 ), diurnal rhythm (Morokuma et al, 2001 ; Kapaya et al, 2018 ), fetal breathing movements (Timor-Tritsch et al, 1977 ), fetal gross movements (van Laar et al, 2014 ), fetal behavioral states (Goncalves et al, 2007 ), smoking (Kapaya et al, 2015 ; Spyridou et al, 2017 ), fetal gender (Bernardes et al, 2008 ; Tendais et al, 2015 ; Goncalves et al, 2017 ), ethnic differences (Marie et al, 2015 ; Tagliaferri et al, 2017 ), and maternal exercise (May et al, 2010 ). Fetal movements of the extremities and trunk, as well as fetal breathing movements, are intermittent and unpredictable; thus, it is especially important to know their influence on the results of FHRV analyses.…”
Section: Introductionmentioning
confidence: 99%